Varistors based on Ta-doped TiO2 - Navale, S. C.; Murugan, A. Vadivel; Ravi, V. (Ceramics International, 2007)
The nonlinear current (I)-voltage (V) characteristics of titanium dioxide are examined when doped with small quantities (0.05-0.5 at.%) of tantalum pentaoxide. For optimum compositions, the nonlinear coefficients are found to be in the range of 25-30 and the breakdown field strength (EB) is similar to 4000 V/cm. The obtained alpha- and E-B-values are higher than the previously reported values for TiO2 ceramics. The acceptor like surface states at the grain boundary adsorb oxygen during sintering and cooling, leading to formation of grain boundary barrier. The grain boundary barrier height (OB) is calculated using Schottky equation. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Oxides; Schottky barrier; TiO2; varistor